California dreaming : ideology, society, and technology in the citrus industry of Palestine, 1890-1939 - Karlinsky, Nahum (State University of New York Press, 2005)
Multidisciplinary study of the citrus industry in Palestine before World War II.
Based on author's doctoral thesis, Hebrew University, 1995.
Keywords: Citrus fruit industry -- Palestine -- History.; Fruit trade -- Palestine -- History.; Entrepreneurship -- Palestine -- History.; Agrumes -- Industrie -- Palestine -- Histoire.; Entrepreneuriat -- Palestine -- Histoire.; BUSINESS & ECONOMICS -- Industries -- Agribusiness.; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture.; Citrus fruit industry; Entrepreneurship; Fruit trade; Middle East -- Palestine; History